Efficacy of steroid pulse therapy for miliary tuberculosis complicated by acute respiratory distress syndrome. (December 2022) - Wakamatsu, Kentaro; Nagata, Nobuhiko; Kumazoe, Hiroyuki; Honjo, Satoshi; Hamada, Minako; Katsuki, Kouta; Hara, Makiko; Nagaoka, Aiko; Noda, Naotaka; Kiyotani, Ruriko; Fukui, Izumi; Ose, Mizuko; et al.
Abstract: Introduction: Acute respiratory distress syndrome (ARDS) is considered a poor prognostic factor for miliary tuberculosis (MTB), but little is known about the effectiveness of steroid pulse therapy for MTB complicated by ARDS. Patients and methods: Medical records were used to retrospectively investigate the prognosis and clinical information of 13 patients diagnosed with MTB complicated by ARDS among 68 patients diagnosed with MTB at our hospital between January 1994 and October 2016. None of the patients had multidrug resistant tuberculosis (TB). MTB was diagnosed by 1 radiologist and 2 respiratory physicians based on the observation of randomly distributed, uniformly sized diffuse bilateral nodules on chest computed tomography and the detection of mycobacterium TB from clinical specimens. ARDS was diagnosed based on the Berlin definition of ARDS. The effect of steroid pulse therapy on death within 3 months of hospitalization was examined using Cox proportional hazards models. Variables were selected by the stepwise method (variable reduction method). Results: Six of 8 patients with MTB complicated by ARDS were alive 3 months after hospitalization in the steroid pulse therapy group, whereas only 1 of 5 patients was alive in the non-steroid pulse therapy group. Analysis of factors related to the survival of patients with MTB complicated by ARDS revealed that steroid pulse therapy was the strong prognostic factor (hazard ratio = 0.136 (95 % CI: 0.023–0.815)). Conclusion: Our findings suggest that steroid pulse therapy improves the short-term prognosis of patients with MTB complicated by ARDS.